Gerakan Literasi Sebagai Strategi Efektif Dalam Menanggulangi Krisis Literasi di Sekolah Dasar - Galuh Nur Insani; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
Elementary school is a time when children are in their golden age, so it is important to instill noble moral values. The literacy movement is one way that can be done to instill noble character. However, in this case there are still many students who lack interest in reading, for this reason this article was created to discuss effective strategies in increasing students' interest in reading. The literacy movement will be successful if it runs holistically. Apart from teachers at schools, parents, libraries, government and the private sector must also work together to support the realization of the literacy movement. Through reading activities in elementary school, students are not only given the opportunity to develop reading skills, but also to form positive reading habits from an early age. Cultural literacy integrated in the reading movement opens students' access to knowledge and stimulates their imagination